The Influence of Religion on Electoral Politics in Ghana: The 2024 General Election - Abdul Shamhuna (Penerbit Hellow Pustaka, 2025)
This paper looks at how religious affiliations and beliefs affect how people vote and which parties they support in the 2024 general elections in Ghana. It focuses on the important role that religious groups play in determining electoral results. The study uses a mixed-methods approach, combining both qualitative and quantitative data. It includes surveys that measure voter preferences, interviews with well-known religious leaders, and a thorough analysis of election results based on religious demographics. The outcomes show that many voters base their choices on their religious beliefs, which greatly influences their party support and voting rates. Importantly, religious leaders are found to be major influencers, rallying backing for certain candidates and parties. This highlights the need for political groups to work with religious organizations in a strategic manner. These findings are especially relevant in the context of healthcare, as voter choices driven by religious beliefs can shape health policy goals and funding decisions. By shedding light on the connection between religion and election politics, this study not only deepens understanding of electoral behaviours in Ghana but also encourages a review of health policy frameworks that may be influenced by these political connections. Therefore, the research could improve political strategies, guiding healthcare advocates and policymakers on how important religious beliefs are in forming public opinion and health-related political goals.